Relationships between components of the 24-hour activity cycle and feelings of energy and fatigue in college students: A systematic review. (October 2021) - Frederick, Ginny M.; O'Connor, Patrick J.; Schmidt, Michael D.; Evans, Ellen M.
Abstract: Problem: College students report high levels of mental and emotional exhaustion. As part of the 24-hour activity cycle (24-HAC), sleep, sedentary behavior (SED), and physical activity are health habits that may exert independent and interactive effects on daily aspects of wellbeing and health in this cohort. The purpose of this systematic review was to synthesize the available evidence on relationships between the individual components of the 24-HAC and feelings of energy and fatigue among college students. Method: Three databases were searched using terms related to sleep, SED, light-intensity physical activity (LIPA), and moderate-to-vigorous physical activity (MVPA), energy, fatigue, and college students. Peer-reviewed, primary studies published in English using valid and reliable measures were included. Results: Fifty-two unique studies were identified for inclusion. Sleep quality and quantity are likely positively associated with feelings of energy and negatively associated with feelings of fatigue; however, studies on LIPA and SED were less common leading to inconclusive findings. Most studies reported on associations between MVPA and feelings of energy or fatigue and indicate positive and negative relationships, respectively. Conclusions: To date, most research has focused on relationships between MVPA and feelings of energy and fatigue. More research is needed to further characterize relationships between the other behavioral components and these outcomes of interest. Additionally, future research should include measurements of all four behavioral components within the framework of the 24-HAC to more fully elucidate how these behaviors interact to impact feelings of energy and fatigue in college students. Highlights: Systematic review of feelings of energy & fatigue & the 24-h activity cycle. Looks at bivariate relationships between behaviors & feelings of energy & fatigue. More studies of sedentary time and light activity are needed. Encourages future research incorporating measurement of the 24-h activity cycle.